Variation in obsessive-compulsive symptoms between children and adults (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The complexity and diversity of clinical manifestations of obsessive-compulsive disorder have intrigued psychiatrists for a long time. Various differences have been noted in the presentation of obsessive-compulsive disorder of different age group. It was aimed to assess the variations of presentation of symptoms in children and adults in a tertiary level hospital. This study was done in an outpatient department from May 2015 to April 2017. Four hundred patients were included in the study consecutively after considering the inclusion and exclusion criteria. Respondents were interviewed with a semi-structured questionnaire which includes demographic variables, psychiatric diagnoses (DSM-IV-TR) and Y-BOCS symptom checklist. Obsessive-compulsive disorder started before adulthood in 41.5% of patients and onset after 18 years was found to be 58.5%. In this study, cases of obsessions, dirt and contamination was seen to predominate in both early- and late-onset obsessive compulsive disorder (68.3 and 71.4% respectively) and among the cases of compulsions, cleaning variety was found to be highest in both early- and late-onset (65.8 and 73.3% respectively). Age should be taken into account when evaluating obsessive compulsive disorder patients. The results suggest that more studies are necessary to determine whether in fact, it defines a homogeneous and particular group in obsessive-compulsive disorder.